PELAKU UMKM DI PONDOK PESANTREN: TINJAUAN FENOMENOLOGIS TERHADAP PANDEMI EFFECT - Moh. Idil Ghufron; Achmad Febrianto; Saifuddin Saifuddin; Siti Ruqayyah; Fathudin Fathudin (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study was to analyze the condition of MSME actors at the Nurul Jadid Islamic boarding school in the Az-Zainiyah region during the Covid-19 pandemic. And to find out the marketing mix strategy used by MSME actors during the Covid-19 pandemic. The research method used is a qualitative research method with a phenomenological approach. To test the validity of the data in this study using data source triangulation techniques. From this research, the results of the Covid-19 Virus have made MSME actors in the Az-Zainiyah area, namely increasing sales, turnover and labor. MSME actors can survive and even increase their business by using a marketing mix strategy with 4 P's, namely product, price, place and promotion. Keywords : Covid-19, MSME, Marketing Mix